Construction of the Al-Miftah Lil Ulum Fast Book Reading Method in Forming Students' Self-Efficacy - Ma'isyah, Mukfiyah; Imami, Agus Sulthoni (Al-Qalam Institue, 2025)
Traditional Islamic book learning tends to emphasize text mastery but pays little attention to students' self-efficacy and learning independence. This study aims to analyze how the Al-Miftah Lil Ulum rapid book reading method influences the self-efficacy and psychological transformation of students through a systematic pedagogical approach based on intrinsic motivation. This study uses a qualitative approach with a case study design. Data were obtained through observation, interviews, and documentation of ustaz and students in the context of book learning in Islamic boarding schools. The results show that the Al-Miftah Lil Ulum method fosters self-confidence and learning independence through gradual success experiences, social and spiritual support, and reflective and collaborative learning interactions. Three main findings emerged: methodological construction based on successful experiences strengthens students' self-efficacy, the internalization of self-efficacy values through social and spiritual support increases motivation and emotional calm, and psychological transformation encourages the formation of sustainable learning autonomy. This study contributes to the development of Islamic pedagogical theory by emphasizing the importance of synergy between cognitive, affective, social, and spiritual dimensions in developing students' learning character, which is characterized by confidence, independence, and resilience.